Space Oriented Approach In Training Architectural Design - Ghayourfar, Alireza; Etesam, Iraj; Mokhtabad, Seyed Mostafa (The Turkish Online Journal of Design Art and Communication, 2016)
Architecture Art improving the human space He lived in the fullness of time. Recognizing the need of every human being and his own existence. This recognition space in the fullness of their permanent and environment is formed. Texture of geometric order, body space Permanent full-time in the objective-subjective paradigm becomes fixed, but always subject to criticism. Review this harmonious interlacing method not only realized later body the space but also the biological aspect of human evolution led to the creation space The architectural essence of architecture education; space , subjective visualization is not enough. Current trends in innovation in architectural education according to subjective body, areas of biological review space independent narrowed because of conception space than being space human and creative role in creating location-dependent variable in the assessment of the measure space Put to the test by coach research paper analysis, coding method creates a conceptual model and interpret data in order to confirm that it benefited. The results indicate the existence of the interrelationship between the environment and people's sense of identity derived from sense perception as the highest grade space.
Keywords: Space; biological space perception; architectural training approach; evaluation criterions space; Uzay; vücut alanı; biyolojik uzay algısı; mimari eğitim yaklaşımı; değerlendirme kriterleri alanı